AFFECTIVE IDENTITY AND RELATIONAL ASYMMETRY IN INDONESIAN POP SONG LYRICS: A DISCOURSE LINGUISTIC ANALYSIS OF SEDIA AKU SEBELUM HUJAN - Lay Riwu; Rawu Yuda Yuwana (PT Akselerasi Karya Mandiri, 2025)
This study examines affective identity and relational asymmetry in contemporary Indonesian pop song lyrics from a discourse linguistic perspective. Drawing on Critical Discourse Analysis (CDA), affective linguistics, and stance theory, the article analyzes Sedia Aku Sebelum Hujan by Idgitaf as a site of affective meaning-making in popular culture. Using qualitative discourse analysis, the study focuses on micro-linguistic features such as pronominal patterns, modalization, metaphorical framing, repetition, and narrative positioning. The findings show that affective identity is constructed through consistent first-person agency (aku) and anticipatory emotional readiness, while the addressee (kau) is positioned as passive. This configuration produces a structurally asymmetrical relational pattern. Metaphors of rain, preparation, and struggle frame emotional devotion as moral responsibility, whereas modal expressions normalize emotional sacrifice as inevitable rather than negotiable. Repetition functions as an affective anchoring strategy that stabilizes and legitimizes unequal emotional labor. This study contributes to linguistic scholarship by demonstrating how affect and power intersect in intimate, non-institutional discourse. By integrating affective linguistics with CDA and applying it to Indonesian popular music, the research highlights song lyrics as influential discursive sites where cultural norms of love, care, and sacrifice are produced and circulated.